Instituția avocaturii la începuturi în România [Articol] - Ciobanu, Igor (CEP USM, 2020)
The right of representation is an institution whose need is subsequently justified by the development and complex relations of social life in the late eighteenth and early eighteenth centuries, with the emergence of social classes to cope with the goods and the holding function of the state, soon became big compact of foreigners. Because of these needs, the representation in justice as an institution seems to confuse its right of defence.
THE INSTITUTION OF ADVOCACY AT THE BEGINNING IN ROMANIA
Keywords: avocat